International Assistance and Media Democratization in the Western Balkans: A Cross-National Comparison - Irion, Kristina; Jusić, Tarik (Global Media Journal - German Edition, 2015)
International media assistance programs accompanied the democratic media transition in Albania, Bosnia and Herzegovina, Kosovo, Macedonia and Serbia with varying intensity. These countries untertook a range of media reforms to conform with accession requirements of the European Union (EU) and the standards of the Council of Europe, among others. This article explores the nexus between the democratic transformation of the media and international media assistance (IMA) as constrained by the local political conditions in the five countries of the Western Balkans. It aims to enhance the understanding of conditions and factors that influence media institution building in the region and evaluates the role of international assistance programs and conditionality mechanisms herein. The cross-national analysis concludes that the effects of IMA are highly constrained by the local context. A decade of IMA of varying intensity is not sufficient to construct media institutions when, in order to function properly, they have to outperform their local context. From today’s vantage point it becomes obvious, that in the short-term scaling-up IMA does not necessarily improve outcomes. The experiences in the region suggest that imported solutions have not been sufficiently cognitive of all aspects of local conditions and international strategies have tended to be rather schematic and have lacked strategic approaches to promote media policy stability, credible media reform and implementation. To a certain extent, the loss of IMA effectiveness is also self-inflicted.